A Content Analysis of Students - Yuliana, Nur Melani; Widiastuty, Hesty (Institut Agama ISlam Negeri Palangka Raya, 2022)
A factor that has an impact on the teaching and learning process is the instructional material. This means that input has typically always been provided by material creators in line with their understanding of how language may be effectively learned through input. This study attempts to determine how well the English textbook